Implementation of building construction permit in So'e city, South Timor Tengah regency (TTS) - Misraim Nubatonis; Petrus Kase; Nursalam Nursalam (Journal of Governance and Accountability Studies, 2021)
Purpose: This study aimed to analyze the implementation of the Building Construction Permit policy and to analyze the inhibiting factors for implementing the Building Construction Permit policy based on the Regional Regulation of South Timor Tengah regency Number 7 of 2015 in So'e city, South Timor Tengah regency. Research methodology: This research was qualitative research using a descriptive approach. The data were collected through interviews, observation and documentation. Results: The inhibiting factor for the implementation of the Building Construction Permit policy in So’e city, South Timor Tengah regency is the limited resources in the form of human resources, financial resources, operational resources, buildings that are not in accordance with spatial planning and many buildings that violate the boundary lines as well as public understanding of building permit regulations. Limitations: This study only analyzed the implementation of the Building Construction Permit policy based on the Regional Regulation of South Timor Tengah regency Number 7 of 2015 in So’e city, South Timor Tengah regency. Contribution: This research becomes scientific information for public administration program.